Serviceability of Reinforced Concrete Gable Roof Beams with Openings under Static Loads - Hassan, M. A. J.; Izzet, A. F. (Engineering, Technology & Applied Science Research, 2019)
This paper presents an analytical study on the serviceability of reinforced concrete gable roof beams with openings of different sizes, based on an experimental study which includes 13 concrete gable roof beams with openings under static loading. For deflection and crack widths under static loading at service stage, a developed unified calculation procedure has been submitted, which includes prismatic beams with one opening subjected to flexure concentrated force. The deflection has been calculated with two methods: the first method calculated deflections via relevant equations and the second was Direct Stiffness Method in which the beam is treated as a structural member with several segments constituting the portions with solid sections and those with sections crossed by the opening. The crack width was calculated with the ACI code’s equation with a proposed magnification factor equal to 1.125. The analytical results were compared with the experimental ones and a good agreement was obtained.